2019
DOI: 10.3390/medicina55010013
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder and Comorbid Borderline Personality Disorder: Patient Characteristics and Outcomes in US Hospitals

Abstract: Background and objectives: The quality of life and disease outcomes in bipolar patients, including increased risk of psychiatric hospitalizations and suicide, are adversely affected by the presence of borderline personality disorder (BPD). Our study aims to determine the impact of BPD on the inpatient outcomes of bipolar disorder patients. Methods: We used Nationwide Inpatient Sample from the US hospitals and identified cases with bipolar disorder and comorbid BPD (N = 268,232) and controls with bipolar disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Females have about 1.6 times higher risk for anxiety and BPD compared to males [11]. About half of the BD patients with comorbid BPD are young adults (18-35 years), and they are at higher needs for acute inpatient care due to suicidal risk [26].…”
Section: Discussionmentioning
confidence: 99%
“…Females have about 1.6 times higher risk for anxiety and BPD compared to males [11]. About half of the BD patients with comorbid BPD are young adults (18-35 years), and they are at higher needs for acute inpatient care due to suicidal risk [26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a large sample retrospective study, Patel and collaborators found that ECT was more frequently administered in bipolar patients with BPD comorbidity than in those without BPD ( P > 0.001). In particular, the parameters evaluated were suicidal ideation, the duration of hospitalization, and the presence of comorbidities that worsen the prognosis, such as substance abuse (Patel et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, the selected studies indicate that the presence of comorbidity may hamper the effectiveness of treatment in BD in terms of longer hospitalization (Swartz et al ., 2005; Patel et al ., 2019), the administration of a second-line pharmacotherapy and ECT, or diminished improvement of symptoms such as hostility (Aguglia et al ., 2018). Of note, these trials assessed the effectiveness of atypical antipsychotics alone or in combination (Martínez and Caballero, 2017; Aguglia et al ., 2018; Garza Guerra et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many variables predict recurrence of illness or poor outcome independent of treatment and may not be crucial in the choice of medication: history of previous episodes, subsyndromal or residual symptoms [ 12 , 25 , 101 , 102 ], alcoholism/substance use [ 12 , 91 ], anxiety [ 12 , 103 ], psychotic features [ 12 , 104 - 106 ], early onset of illness, [ 107 ], mixed features [ 108 - 110 ], rapid cycling course [ 12 , 111 , 112 ], personality comorbidity [ 12 , 113 ].…”
Section: Limitationsmentioning
confidence: 99%